COORDINATION AND DISASTER MANAGEMENT IN PUBLIC ADMINISTRATION: AN EVALUATION ON THE DISCUSSIONS OF MINISTRY OF DISASTER (Third Sector Social Economic Review, 2023)
The aim of this study is to evaluate and discuss the establishment of a ministry through which public administration can achieve effective and constructive results in disasters in Turkey. Public administration is the largest, most comprehensive and most complex structure of a country to serve its citizens. The importance of coordination is that despite this complexity in public administration, it continues to provide the determined and intended services to the citizens; it depends on the ability of the units within itself to continue their actions in a strong network of relations so that there is no gap in service provision. Coordination is of vital importance for public administration in extraordinary periods rather than ordinary periods. The key point here is the specialized public administrations that will solve the negative situations caused by extraordinary consequences such as disasters at the local scale. In this study, the discussions on the establishment of a Ministry of Disaster have been evaluated in this context. Establishment of a Ministry of Disaster will not eliminate the reality of disasters, nor will it affect the frequency of disasters. Rather than a public administration unit that will manage only the consequences of disasters, a structure that will minimize the negative consequences of disasters and has the mechanisms to transform the process leading to disasters into positive externalities is essential for Turkish public administration. In conclusion, the specialization of public administration units in their relevant fields and their ability to involve other public administration units in a coordinated manner during extraordinary periods such as disasters are directly linked to the professionalization of institutions in all aspects and the merit of those who manage the process.
Keywords: Public Administration; Coordination; Disaster; Disaster Management; Ministry of Disaster